PENGEMBANGAN KARAKTER PESERTA DIDIK MELALUI PELAYANAN BIMBINGAN DAN KONSELING - Linda Yani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
The problems that occur of learners in the modernization era increasingly complex. This condition is seen from various phenomena that occur in social life of society. Implemented program in character building of this student, it becomes an important part for our nation forward, especially learners. Education is done until now, the results have not been as expected. There are still many occurrences of events that have an effect on the lives of learners in terms of deviant behavior such as drug use, sexual harassment, aggressive behavior, brawl, bullying, fight between one to another and etc. Character education materials are loaded into each subject, local content and Guidance and Counseling services. Counselor Teachers / Counselors are responsible for the learning activities associated with BK services for a number of learners. Individual character development can be done by professional guidance and counselor/counselor in guidance and counseling. The type of research used descriptive qualitative research that describes the various data obtained from observations and interviews while the research method of data collection by interview and documentation observation method. The subject of this research is 1 person of guidance and counseling teacher, Head of SMP N 3 Palembang and 7 learners. The result of this research is to know the forms of BK teacher activities and activities in schools such as: Reading Al-Quran, Sholat Ashar congregation, and the existence of individual and group guidance everyday.